Problemy kształtowania obszaru metropolitalnego Lublina - Polski, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Setting back limitations and barriers of development depends on the effectiveness of policy and spatial planning in government and self-government sphere. Previous planning actions concerning scheduled shaping of spatial order in metropolitan areas of cities have been ineffective. It is well seen on the example of Lublin agglomeration for which, in 90s, planning conception was created. It has been taken into account in a valid plan of spatial arrangement for the lubelskie voivodship. On the contrary this conception has hardly been taken into consideration by local spatial planning. The whole idea of scheduled shaping of metropolitan area of Lublin is ineffective. There is a need of change in appropriate law acts and in the organization of co-operation between voivodship self-government and local self-governments (gminas) in this domain. In the author's opinion it is conclusion adequate to planning of the majority of metropolitan areas in Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 146-154